2010
DOI: 10.2113/gssgfbull.181.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary compound incised valleys of the Roussillon coast (SE France): correlation of seismic data with core data

Abstract: A detailed study of a Pliocene to Quaternary incised-valley system located under the Roussillon coastal area (Gulf of Lion) is carried out by means of a high-resolution seismic data set (coastal lagoons and adjacent shelf area), drill reports and analysis of a cored drill (Leucate SC1) performed in 2007 on the barrier beach in the North of Leucate lagoon.The lowermost surface (S100/S200), correlated with a pebbles level on the Leucate core SC1 (R0), erosionnally overlies pliocene deposits. It is incised by a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The detailed analysis and interpretation of seismic data of the incisedvalley system and inner shelf were published recently (Labaune et al 2008;Labaune et al 2010;Tesson et al 2010). These results were integrated in a regional framework including the analysis and interpretation of mid-and outer-shelf areas (Posamentier et al 1992;Tesson et al 2000).…”
Section: Seismic Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed analysis and interpretation of seismic data of the incisedvalley system and inner shelf were published recently (Labaune et al 2008;Labaune et al 2010;Tesson et al 2010). These results were integrated in a regional framework including the analysis and interpretation of mid-and outer-shelf areas (Posamentier et al 1992;Tesson et al 2000).…”
Section: Seismic Results and Interpretationmentioning
confidence: 99%
“…Pliocene Deposits.-These have been identified under the coastal plain and beach barrier (Duvail et al 2002;Duvail et al 2005;Duvail 2008) over numerous long drills logs (several hundred) stored by the Bureau de Recherches Géologiques et Minières (BRGM) and correlated with seismic profiles obtained in the Leucate lagoon and the tidal channel (Labaune 2005;Tesson et al 2005;Labaune et al 2009;Tesson et al 2010). Seismic facies present (Fig.…”
Section: Coastal Plain and Inner Shelfmentioning
confidence: 86%
See 1 more Smart Citation
“…Note the position of core GL-854 with the small blue square (D) Sea level variations during the Pliocene and Quaternary (Miller et al, 2020) with the main climatic event. INHG: Initiation of Norther Hemisphere Glaciations, MPT: Mid-Pleistocene Transition; MBE : Mid Brunhes Event; MIS Marine Isotopic Stage. The relationship between Late Quaternary margins' stratigraphy and sea level changes is well-documented from high resolution seismic data over the world, especially for the last few 100 kacycles (e.g., Kolla et al, 2000;Schuur Duncan et al, 2000;Liu et al, 2004;Rabineau et al, 2005Rabineau et al, , 2006Berne et al, 2007;Ridente et al, 2008;Bassetti et al, 2008;Tesson et al, 2010;Le Roy et al, 2014;Lafosse et al, 2018). Several studies have been conducted on the continental shelf of Rio de Janeiro State (e.g., Pinheiro-Moreira et al, 2001;Artusi et al, 2007;Fleming et al, 2009;Maia et al, 2010;Reis et al, 2013) and suggested that the continental shelf of the Santos Basin also offers the opportunity to examine the relationship between the architecture of the Quaternary deposits and the 100 ka glacio-eustatic cycles.…”
Section: Introductionmentioning
confidence: 99%